2013
DOI: 10.1161/hypertensionaha.113.01561
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Distinct Components of Increased Blood Pressure on Cardiovascular Outcomes

Abstract: Elevation in blood pressure (BP) increases risk for all cardiovascular events. Nevertheless, the extent to which different indices of BP elevation may be associated to varying degrees with different cardiovascular outcomes remains unclear. We studied 13,340 participants (aged 54±6 years, 56% women, 27% black) of the Atherosclerosis Risk in Communities Study who were free of baseline cardiovascular disease. We used Cox proportional hazards models to compare the relative contributions of systolic (SBP), diastoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…In addition, the SPRINT trial excluded patients with diabetes and previous stroke, who were included in our study . With regards to DBP, our study found that DBP at baseline was not a significant predictor of adverse CV outcomes, and there are studies that have reported similar findings of better predictive power of SBP over DBP in predicting CV outcomes …”
Section: Discussionsupporting
confidence: 59%
“…In addition, the SPRINT trial excluded patients with diabetes and previous stroke, who were included in our study . With regards to DBP, our study found that DBP at baseline was not a significant predictor of adverse CV outcomes, and there are studies that have reported similar findings of better predictive power of SBP over DBP in predicting CV outcomes …”
Section: Discussionsupporting
confidence: 59%
“…However, women still tended to have more prevalent hypertension as well as a higher associated CVD risk, even by 1996-1998; this finding could be related to the greater proportion of isolated systolic hypertension and arterial stiffness in women than men. 29-31 Despite similar trends to men in the decreasing prevalence of smoking and increasing prevalence of obesity, women tended to display consistently higher hazards of CVD risk associated with both of these risk factors over time. Most importantly, the CVD risk attributable to diabetes remained significantly higher in women than men over time, driven by higher associated hazards despite lower prevalence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent prehypertension (defined as BP of 120-139/80-89 mm/Hg) and more so hypertension (BP of 4140/490 mm/Hg) is one of the risk factors for several diseases and disorders and may contribute significantly to the development of leading factors of death in the Western world such as heart failure and stroke (Huang et al, 2014). In addition, hypertension increases the risk of atherosclerosis (Cheng et al, 2013) and chronic kidney disease (Segura & Ruilope, 2011).…”
Section: Introductionmentioning
confidence: 99%